Peculiarities of human resource management in social service organizations in Ukraine under martial law - Buhai, Kateryna (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2024)
The article examines the important issue of human resource management in social service organizations in the current working environment characterized by a large flow of migration, military operations and shelling, the emergence of new categories of clients in need of assistance, and high levels of stress. The article substantiates the importance of maintaining the emotional state of employees along with the introduction of new methods of personnel management to reduce the impact of negative factors on the activities of social service professionals. The purpose of this article is to identify the peculiarities of personnel management in social service organizations under martial law in Ukraine, to characterize human resource management practices, and to determine their shortcomings in order to outline relevant directions for development. Based on the results of the qualitative analysis of the reconnaissance sociological study “Human Resources Management in Social Service Organizations in Kharkiv Region”, the main problems in the system of human resources management of such organizations are identified, and the main needs for changing the methods of human resources management are outlined. The author’s of the article consider the features of the personnel management system in social service organizations, namely its components (planning, personnel selection, personnel adaptation, motivation, training, personnel certification and evaluation, dismissal). The article also analyzes the methods of working with personnel in organizations of the social sphere. On the basis of the presented material, a conclusion is made about the importance and necessity of improving the personnel management system in social service organizations, namely in the modernization and adaptation of the system of motivation, adaptation and selection of personnel to modern working conditions. And maintaining the emotional state of employees in the conditions of martial law should also occupy a priority position among personnel management methods.